ANALYZE ERRORS WHEN USING PERSONAL PRONOUNS FLUENTLY IN THE FIRST SEMESTER OF THE ENGLISH DEPARTMENT - Roni Roni; Kassaming Kassaming; Baharuddin Baharuddin; Arsyad Arsyad (La Ogi : English Language Journal, 2021)
English learners not only need to be aware of the present and future but also need to be aware of the difficulties and problems they encounter in the process of learning English. Especially in the use of parts of speech, called pronouns. The purpose of this study is to collect and analyze the errors made by students in the form of markers, to serve as a reference for the mastery of pronouns in which the teaching and learning methods necessary to achieve The expected target in the document will be added to the grammar itself. This study was conducted in 2015 in the UMTS teaching and education department of 38 students. Data can be obtained from grammar placement tests and student interviews. Even if students are at an intermediate level of English, participating in grammar lessons is necessary. The research findings suggest that there is a place in language, especially in discussions of personal pronouns, that is certainly worth highlighting. Students' errors and comments about their problems are very useful signs or important diagnoses. The use of data is that as long as the information has a direct connection to the student, the professor can build a plan that allows the student to expand their knowledge and can help them become more confident in professional communication. Karma. It is very important and helpful to benefit from an English education major, as it is an extraordinary source of motivation for students